2021
DOI: 10.31234/osf.io/yqtd9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What do our sampling assumptions affect: how we encode data or how we reason from it?

Abstract: In describing how people generalize from observed samples of data to novel cases, theories of inductive inference have emphasized the learner's reliance on the contents of the sample. More recently, a growing body of literature suggests that different assumptions about how a data sample was generated can lead the learner to draw qualitatively different inferences on the basis of the same evidence. Yet relatively little is known about how and when these two sources of evidence are combined. For instance, do sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Instilling a sense of distrust about the misinformation source's motives may also be more effective at encoding than at retrieval (i.e., when misinformation is encoded rather than when the correction is presented). This explanation also fits with recent work showing that people are better able to incorporate information about constraints on a sample of evidence when it presented at encoding than when presented at retrieval (Ransom et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Instilling a sense of distrust about the misinformation source's motives may also be more effective at encoding than at retrieval (i.e., when misinformation is encoded rather than when the correction is presented). This explanation also fits with recent work showing that people are better able to incorporate information about constraints on a sample of evidence when it presented at encoding than when presented at retrieval (Ransom et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The latter condition should mean that the frames instructions were easier to retrieve for the generalization test. Ransom et al (in press), however found a weaker sampling frames effect in the ‘after’ compared with the ‘before’ condition. Hence, it seems unlikely that retrieval of frames instructions at the time of testing is a key factor in determining generalization performance.…”
Section: Discussionmentioning
confidence: 77%
“…The Ransom et al (in press) results imply that applying frames instructions as sample instances are encoded is crucial. Superior working memory ability memory may impact this process by making it easier to encode each sample instance and to use this information to update the probabilities of rival hypotheses about property extension (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the research investigating sampling assumptions has focused on how people reason from weak or strong samples. Under weak sampling, examples have been randomly sampled from the world and then labelled, while under strong sampling, they are randomly sampled from the category being learned (Anderson, 1981;Hendrickson et al, 2019;Navarro et al, 2012;Ransom et al, 2021;Tenenbaum & Griffiths, 2001). While this research is useful for beginning to think about what assumptions underlie people's ability to make rich inferences from sparse data, realistic scenarios encompass a range of assumptions that go beyond strong and weak alone.…”
Section: Introductionmentioning
confidence: 99%